Safety Problem- a Factor in Successful Functioning of the Shipping Industry - Rudić, Dušan (Promet - Traffic&Transportation, 2012)
Continual growth of world maritime trade involves thegrowth of world shipping-industry capacities. This growth impliesnot only bigger ships and greater overall capacities, butalso some technical and technological changes that includenew ships, specialisation and development of new technologieswithin the maritime traffic.Due to complex navigation conditions, newer and more expensiveships that represent very complex and sensitive objects,the competition and human factor, the safety problem has oftenbeen out of control.The governments of countries within /MO and ILO increasinglyintroduce new rules and conventions to enhancenavigation safety. However, in view of economic-financial effects,many shipping companies overlook the safety problem.The most recent revision of STCW Convention and theISM Code implementation, which are becoming operative inthe current years, aim to increase the overall culture of qualitymanagement (QM) and to enhance the safety management onships and in maritime companies.